Working for a Good Cause - Robert Dur; Robin Zoutenbier (Center for Economic Studies and ifo Institute (CESifo), 2013)
A rich literature in public administration has shown that public sector employees have stronger altruistic motivations than private sector employees. Recent economic theories stress the importance of mission preferences, and predict that altruistic people sort into the public sector when they subscribe to its mission. This paper uses data from a representative survey among more than 30.000 employees from 50 countries to test this prediction. We find strong evidence for a mutually reinforcing role of altruism and mission alignment in sorting to the public sector, particularly among highly educated workers and among workers in less-developed countries.
Keywords: H10; J45; M50; 330; public service motivation; altruism; mission preferences; sorting; World Values Survey